APLIKASI PELAYANAN PELANGGAN PDAM TIRTA MAYANG KOTA JAMBI BERBASIS ANDROID - Pariyadi, Pariyadi; Astuti, Reny Wahyuning; Syarif, Nanang Maulana (FORTECH (Journal of Information Technology), 2019)
PDAM or Perusahaan Daerah Air Minum Tirta Mayang is one of the regional owned business units engaged in the distribution of clean water for the general public in Jambi City. In terms of service, there are some parts that are still done manually and are less effective, for example in the case of new pairs registration and complaints that are still done manually, the customer must come to the PDAM Tirta Mayang office, which of course takes a lot of time and energy, also limited only when office open. Therefore we need a mobile application that can access all customer services online in order to provide optimal service. This service application will be designed consisting of mobile applications made using Android Studio and web admin using PHP. By entering data input, in the form of customer data, billing data, complaint data. while the output produced is in the form of customer account reports, complaint reports, and complaint recap reports. The design of this website is done in full so that it can cover all needs. The expected results of this research are the Android Service Application of PDAM Tirta Mayang, Jambi City which is able to provide information quickly, and provide the best service.